Successfully Striving for Happiness: Socially Engaged Pursuits Predict Increases in Life Satisfaction - Julia M. Rohrer; David Richter; Martin Brümmer; Gert G. Wagner; Stefan C. Schmukle (Psychological Science, 2018)
Happiness is considered a highly desirable attribute, but whether or not individuals can actively steer their lives toward greater well-being is an open empirical question. In this study, respondents from a representative German sample reported, in text format, ideas for how they could improve their life satisfaction. We investigated which of these ideas predicted changes in life satisfaction 1 year later. Active pursuits per se—as opposed to statements about external circumstances or fortune—were not associated with changes in life satisfaction (n = 1,178). However, in line with our preregistered hypothesis, among individuals who described active pursuits (n = 582), those who described social ideas (e.g., spending more time with friends and family) ended up being more satisfied, and this effect was partly mediated by increased socializing. Our results demonstrate that not all pursuits of happiness are equally successful and corroborate the great importance of social relationships for human well-being.
Keywords: 330; happiness; life satisfaction; interpersonal relationships; well-being; pursuit of happiness; open data; open materials; preregistered